2014
DOI: 10.4103/0259-1162.128923
|View full text |Cite
|
Sign up to set email alerts
|

Unanticipated cardiac arrest under spinal anesthesia: An unavoidable mystery with review of current literature

Abstract: Cardiac arrest during anesthesia and perioperative period is a matter of grave concern for any anesthesiologist. But such mishaps have been reported for one reason or the other in the literary sciences. We are reporting the occurrence of unanticipated delayed cardiac arrest following spinal anesthesia in two young and healthy patients. Fortunately, these patients were successfully resuscitated with timely and appropriate cardiopulmonary resuscitative measures. Occurrence of such cases needs timely reporting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Spinal anesthesia is considered to be a safe procedure but complications rarely can occur in the clinical scene [ 1 , 2 ]. Ever since Caplan et al [ 6 ] reported 14 cases of cardiac arrest during spinal anesthesia in an American Society of Anesthesiologists closed claim analysis, numerous case reports and reviews have been published [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal anesthesia is considered to be a safe procedure but complications rarely can occur in the clinical scene [ 1 , 2 ]. Ever since Caplan et al [ 6 ] reported 14 cases of cardiac arrest during spinal anesthesia in an American Society of Anesthesiologists closed claim analysis, numerous case reports and reviews have been published [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ever since August Bier administered the first clinical spinal anesthesia more than a century ago, it has become an integral part of the modern day anesthesia practice. Although considered simple to perform and a relatively safe technique, life-threatening complications do occur under spinal anesthesia [ 1 , 2 ]. In the literature, the reported incidence of cardiac arrest is 1.3–18 in 10,000 patients [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most serious complications of spinal anesthesia is cardiac arrest [ 17 19 ]. The cardiologist suggested the possibility of cardiac arrest in this case.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports in the literature of cardiorespiratory arrest right after spinal anesthesia. The rate of complications is inherent to the clinical condition of the patient, the surgical pathology, or reached height of the anesthetic block, however there are reports of cardiorespiratory arrest after spinal anesthesia in healthy patients without previous comorbidities 3,4 . Early identification of greater propensity for complications is essential to reduce the time between diagnosis and conduct, implying a reduction in morbidity and mortality 1,3,4 .…”
Section: What Do These Findings Mean?mentioning
confidence: 99%
“…2 Departmento de Anestesiologia, Hospital Universitário Júlio Bandeira (HUJB) -Cajazeiras (PB), Brasil. 3 Faculdade de Medicina Estácio de Juazeiro do Norte (Estácio FMJ) -Juazeiro do Norte (CE), Brasil. Figure 1: Spectral analysis of a patient from rest to discharge of the PACU, demonstrating a return of the autonomic function after the return of the motor function posterior to the subarachnoid anesthesia.…”
unclassified